A method for preparing a porous material loaded with a noble metal catalyst by a template method
By using environmentally friendly materials such as yeast and TS-1 molecular sieve, the preparation of porous material-loaded precious metal catalysts is solved, and the problems of expensive template agents and environmental pollution in traditional methods are achieved, and efficient and environmentally friendly catalyst preparation is achieved.
Patent Information
- Application Number
- CN202411661441.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-04
AI Technical Summary
In the existing preparation methods for precious metal catalysts, template agents are usually expensive, have a long preliminary preparation time, and are prone to environmental pollution, making it difficult to achieve environmentally friendly and efficient catalyst preparation.
Yeast is used as a biological template to generate carbon dioxide by gelatinizing starch, forming pores, increasing porosity, and using TS-1 molecular sieve as a carrier to adsorb and fix Pt to improve the active site, thereby improving the rate and efficiency of selective hydrogenation performance.
The environmentally friendly and efficient preparation of porous material-loaded precious metal catalysts is achieved, which improves the catalytic efficiency and selectivity, and avoids environmental pollution and high cost problems in traditional methods.
Smart Images

Figure BDA0005143470260000081 
Figure BDA0005143470260000091 
Figure BDA0005143470260000092
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a method for preparing a porous material-loaded noble metal catalyst using a template method. Background Art
[0002] Precious metal catalysts are an indispensable raw material in the process of chemical synthesis and are widely used in the synthetic pharmaceutical industry, new materials and fine chemicals. Especially in the face of increasingly stringent environmental protection and process safety requirements, precious metal catalysts have high selectivity and relatively low reaction conditions. At the same time, they have high value, which requires precious metal catalysts to be recycled. Therefore, on the one hand, they have become necessary catalysts in more and more customized syntheses. On the other hand, precious metal catalysts are constantly replacing some highly polluting non-ferrous metal catalysts (such as iron, nickel, and mercury catalysts) and are being used more and more widely.
[0003] Precious metal catalysts are precious metal materials that can change the speed of chemical reactions without participating in the final product of the reaction. Almost all precious metals can be used as catalysts, but platinum, palladium, rhodium, silver, ruthenium, etc. are commonly used, among which platinum (Pt) is the most widely used. Its d electron orbits are not filled, and the surface is easy to adsorb reactants with moderate strength, which is conducive to the formation of intermediate "active compounds". It has high catalytic activity and also has comprehensive excellent properties such as high temperature resistance, oxidation resistance, and corrosion resistance, making it the most important catalyst material.
[0004] According to the type of catalytic reaction, precious metal catalysts can be divided into two categories: homogeneous catalysis and heterogeneous catalysis. Catalysts for homogeneous catalysis are usually soluble compounds (salts or complexes), such as palladium chloride, rhodium chloride, palladium acetate, carbonyl rhodium, triphenylphosphine rhodium chloride, etc. Catalysts for heterogeneous catalysis are insoluble solids, and their main form is a porous inorganic carrier loaded with metal, such as Pt / A12O3, Pd / C, Ag / Al2O3, Rh / SiO2, Pt-Pd / Al2O3, Pt-Rh / Al2O3, etc. In the entire catalytic reaction process, heterogeneous catalytic reactions account for 80% to 90%. At present, it is common to use porous materials to load precious metal catalysts. Among them, the template synthesis method is to use a substance with a nanostructure and easy-to-control shape as a template, and deposit the relevant material into the pores or surface of the template by physical or chemical methods, and then remove the template to obtain a material with the size and structure of the template. The advantage is that the material morphology can be regulated. Among them, common templates include MOF materials, polymer materials, etc. However, these templates are usually expensive, take a long time to prepare, and are prone to environmental pollution. The bio-template method is an environmentally friendly emerging template, which is studied in the present invention. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a method for preparing porous materials loaded with precious metal catalysts by a template method, wherein the porous materials are loaded with precious metal catalysts, and yeast is used as a biological template. At the same time, yeast can also utilize gelatinized starch to produce carbon dioxide, form pores, and increase porosity. TS-1 molecular sieve is used as a loading agent. TS-1 molecular sieve has a large specific surface area and rich microporous structure, and can adsorb and fix Pt, increase active sites, and thus improve the rate and efficiency of selective hydrogenation performance.
[0004] Technical solution: A method for preparing a porous material loaded with a precious metal catalyst by a template method, which comprises the following steps, in parts by weight: S1: Take potato starch, add water to make 80 parts of starch emulsion solution, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain gelatinized starch solution; S2: Take 0.2-0.4 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; S3: Take 0.2-0.5 parts of activated yeast, dissolve it in water, add it dropwise to the mixed solution, seal it, and stir it at 30°C for 4 hours; S4: Transfer to a 4°C refrigerator and allow to stand for 20-22 hours to obtain a starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: adding the porous starch-based carbon aerogel to ethylene glycol and stirring for 30 min, adding potassium chloroplatinate solution, and stirring at room temperature for 2 h; S8: adjusting the pH to 12 with NaOH ethylene glycol solution, heating and stirring at 130 °C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Furthermore, the mass fraction of the starch emulsion solution in S1 is 15-20%. Furthermore, the TS-1 molecular sieve in S2 has a grain size of 200-350 nm, a pore size of 0.56-0.58 nm, and a BET specific surface area of 350-450 m 2 / g. Furthermore, the activation conditions of the yeast in S3 are: activation temperature is 38° C., and activation time is 30 min. Furthermore, the mass ratio of the porous starch-based carbon aerogel, ethylene glycol and potassium chloroplatinate solution in S7 is 1:30:(2-3). Furthermore, the mass fraction of platinum in the potassium chloroplatinate solution in S7 is 5-10%. The porous material prepared by the above method carries a noble metal catalyst. Beneficial effects: 1. The present invention adopts porous materials to load precious metal catalysts and uses yeast as a biological template. At the same time, yeast can also use gelatinized starch to produce carbon dioxide, form pores, and increase porosity. TS-1 molecular sieve is used as a loading agent. TS-1 molecular sieve has a large specific surface area and rich microporous structure, which can adsorb and fix Pt, increase active sites, and thus improve the rate and efficiency of selective hydrogenation performance. 2. The present invention uses yeast as a biological template, which can not only use gelatinized starch to form pores, but also uses gelatinized starch as a precursor and a nano-micro carrier of TS-1 molecular sieve to polymerize the material on the surface of the full-bodied yeast cell, thereby avoiding agglomeration. At the same time, during the roasting process, the cell structure volatilizes, leaving a nano-micro cavity structure, which forms smaller and more uniform mesopores, increases the specific surface area, thereby providing more active sites, and thus improving the catalytic efficiency and selectivity. 3. The present invention uses gelatinized starch as a raw material to prepare aerogel, which is then sintered to form a large number of internal pores, greatly increasing the specific surface area, providing a large number of active sites, and helping to improve the activity of the catalyst. DETAILED DESCRIPTION Example 1 A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 15%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.3 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Take 0.4 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the mixed solution, seal, and stir at 30℃ for 4h; S4: transfer to a 4°C refrigerator and allow to stand for 21 hours to recover the starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Example 2 A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.3 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Take 0.4 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the mixed solution, seal, and stir at 30℃ for 4h; S4: transfer to a 4°C refrigerator and allow to stand for 21 hours to recover the starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Example 3 A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.2 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Take 0.4 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the mixed solution, seal, and stir at 30℃ for 4h; S4: transfer to a 4°C refrigerator and allow to stand for 21 hours to recover the starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Example 4 A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.4 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Take 0.4 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the mixed solution, seal, and stir at 30℃ for 4h; S4: transfer to a 4°C refrigerator and allow to stand for 21 hours to recover the starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Example 5 A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.3 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Take 0.2 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the mixed solution, seal, and stir at 30℃ for 4h; S4: transfer to a 4°C refrigerator and allow to stand for 21 hours to recover the starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Example 6 A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.3 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Take 0.5 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the mixed solution, seal, and stir at 30℃ for 4h; S4: transfer to a 4°C refrigerator and allow to stand for 21 hours to recover the starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Example 7 A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.3 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Take 0.4 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the mixed solution, seal, and stir at 30℃ for 4h; S4: transfer to a 4°C refrigerator and allow to stand for 21 hours to recover the starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 2 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Example 8 A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.3 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Take 0.4 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the mixed solution, seal, and stir at 30℃ for 4h; S4: transfer to a 4°C refrigerator and allow to stand for 21 hours to recover the starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 10% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst. Comparative Example 1 The difference between this embodiment and embodiment 2 is that TS-1 molecular sieve powder is not added, specifically as follows: A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.4 parts of activated yeast, the activation conditions of the yeast are: activation temperature is 38℃, activation time is 30min, dissolve in water, add dropwise to the gelatinized starch solution, seal, and stir at 30℃ for 4h; S3: Transfer to a 4°C refrigerator and let stand for 21 hours to obtain a starch-based hydrogel; S4: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 hours, then quickly demolded, and freeze-dried at -50°C for 24 hours to obtain a porous starch-based aerogel; S5: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S6: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S7: adjust the pH to 12 with NaOH ethylene glycol solution, heat and stir at 130 °C for 5 h; S8: After filtration and washing, the porous material is dried under vacuum at 80°C to obtain a precious metal catalyst loaded thereon. Comparative Example 2 The difference between this embodiment and embodiment 2 is that no activated yeast is added, specifically as follows: A method for preparing a porous material loaded with a noble metal catalyst by a template method, in parts by weight, comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution with a mass fraction of 20%, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain a gelatinized starch solution; S2: Take 0.3 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; the TS-1 molecular sieve has a crystal size of 200-350nm, a pore size of 0.56-0.58nm, and a BET specific surface area of 350-450m 2 / g; S3: Transfer to a 4°C refrigerator and let stand for 21 hours to obtain a starch-based hydrogel; S4: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 hours, then quickly demolded, and freeze-dried at -50°C for 24 hours to obtain a porous starch-based aerogel; S5: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S6: Add 1 part of porous starch-based carbon aerogel to 30 parts of ethylene glycol and stir for 30 minutes, add 3 parts of 8% potassium chloroplatinate solution, and stir at room temperature for 2 hours; S7: adjust the pH to 12 with NaOH ethylene glycol solution, heat and stir at 130 °C for 5 h; S8: After filtration and washing, the porous material is dried under vacuum at 80°C to obtain a precious metal catalyst loaded thereon. The Pt loading amount of the porous material loaded with the precious metal catalyst of each embodiment was measured, and the results are shown in Table 1 below: Table 1 The selective hydrogenation performance of the porous material-supported noble metal catalyst of each embodiment was measured, and the results are shown in Table 2 below: Table 2
Claims
1. A method for preparing a porous material loaded with a noble metal catalyst by a template method, characterized in that: By weight, the method comprises the following steps: S1: Take potato starch, add water to make 80 parts of starch emulsion solution, heat to 95°C, stir and gelatinize at a speed of 600r / min for 20min to obtain gelatinized starch solution; S2: Take 0.2-0.4 parts of TS-1 molecular sieve powder, add 5 parts of anhydrous ethanol, disperse evenly by ultrasonication, slowly pour into the gelatinized starch solution, stir for 10-20 minutes, and obtain a mixed solution; S3: Take 0.2-0.5 parts of activated yeast, dissolve it in water, add it dropwise to the mixed solution, seal it, and stir it at 30°C for 4 hours; S4: transfer to a 4°C refrigerator and allow to stand for 20-22 hours to obtain a starch-based hydrogel; S5: The starch-based hydrogel was transferred to a -25°C refrigerator and frozen for 10 h, then quickly demolded, and freeze-dried at -50°C for 24 h to obtain a porous starch-based aerogel; S6: placing the porous starch-based aerogel in a tubular furnace, heating the temperature to 800°C at a rate of 5°C / min under N2 flow protection and keeping the temperature for 1 hour, and cooling the temperature to room temperature under N2 atmosphere to obtain a porous starch-based carbon aerogel; S7: adding the porous starch-based carbon aerogel to ethylene glycol and stirring for 30 min, adding potassium chloroplatinate solution, and stirring at room temperature for 2 h; S8: Adjust the pH to 12 with NaOH ethylene glycol solution, and heat and stir at 130°C for 5 h; S9: After filtration and washing, vacuum drying is performed at 80°C to obtain a porous material loaded with a precious metal catalyst.
2. The method for preparing a porous material loaded with a noble metal catalyst by a template method according to claim 1, characterized in that: The mass fraction of the starch emulsion solution in S1 is 15-20%.
3. The method for preparing a porous material loaded with a noble metal catalyst by a template method according to claim 1, characterized in that: The TS-1 molecular sieve in S2 has a grain size of 200-350 nm, a pore size of 0.56-0.58 nm, and a BET specific surface area of 350-450 m 2 / g.
4. The method for preparing a porous material loaded with a noble metal catalyst by a template method according to claim 1, characterized in that: The activation conditions of the yeast in S3 are: activation temperature is 38° C., and activation time is 30 min.
5. The method for preparing a porous material loaded with a noble metal catalyst by a template method according to claim 1, characterized in that: The mass ratio of the porous starch-based carbon aerogel, ethylene glycol and potassium chloroplatinate solution in S7 is 1:30:(2-3).
6. The method for preparing a porous material loaded with a noble metal catalyst by a template method according to claim 1, characterized in that: The mass fraction of platinum in the potassium chloroplatinate solution in S7 is 5-10%.
7. A porous material loaded with a noble metal catalyst prepared by the method according to any one of claims 1 to 6.